Natural history of the fireflies of the Serra dos Órgãos mountain range (Brazil: Rio de Janeiro) – one of the 'hottest' firefly spots on Earth, with a key to genera (Coleoptera: Lampyridae). Issue 5 (1st February 2020) - Silveira, Luiz F L; Khattar, Gabriel; Vaz, Stephanie; Wilson, Vinicius A.; Souto, Paula M.; Mermudes, José R. M.; Stanger-Hall, Kathrin F.; Macedo, Margarete V.; Monteiro, Ricardo F.
ABSTRACT: Fireflies (Coleoptera: Lampyridae) are charismatic insects that have been fruitful model systems in biotechnology. However, lack of information about firefly taxonomy and ecology renders species identification a hard task, especially in the Neotropical region, where fireflies are most diverse. A major gap in the literature on Neotropical fireflies is the lack of knowledge on species' ecological niches and habitats, which are fundamental aspects for understanding their biology. Here, we provide an annotated checklist of the firefly fauna of the Serra dos Órgãos mountain range (Rio de Janeiro State, Southeastern Brazil), with information on the natural history of each species. We assembled data in three ways: monthly sampling with Malaise traps and active search along an elevational transect from 130 to 2, 170 m, over 2 years (2014–2016), extensive field observations, and extracted from historical species records for the Serra dos Órgãos from museum specimens in key collections in Brazil and Europe. We provide a taxonomic key to the genera recorded in the region, and a differential diagnosis for each species, highlighting key references for each taxon. We report 58 species representing 21 genera, making the Serra dos Órgãos one of the richest firefly hotspots on Earth. Most species are restricted to one or two habitat types and/or just one of the regional seasons (warm or cool), and many were only collected either by malaise traps or active search, underlining the importance of sampling different habitat types and seasons, and using different sampling methods when surveying fireflies. Out of the 51 species observed in the field, 49 were active either during the day or the night, although two species – Photuris elliptica and Pyrogaster nigrolineatus – were active in both periods, which is rare in fireflies.